Forage yield and nutritive value of Panicum maximum genotypes in the Brazilian savannah - Francisco Duarte Fernandes; Allan Kardec Braga Ramos; Liana Jank; Marcelo Ayres Carvalho; Geraldo Bueno Martha Jr.; Gustavo José Braga (Scientia Agricola, 2014)
The narrow genetic variability of grasslands and the incidence of new biotic and abiotic stresses have motivated the selection of new Panicum maximum genotypes for use as forage for beef cattle in the Brazilian savannah. This study aimed to evaluate forage yield and nutritive value of P. maximum genotypes including 14 accessions (PM30 to PM43), four intraspecific hybrids (PM44 to PM47) and six cultivars (Aruana, Massai, Milênio, Mombaça, Tanzania and Vencedor), examining 24 genotypes over two years (2003 and 2004). Milênio cultivar was the genotype with the highest dry matter yield (DMY) in both years (18.4 t ha-1 and 20.9 t ha-1, respectively) although it presented a high proportion of stems (~ 30%). Genotypes that showed higher Leaf DMY in both years were the accession PM34 (14.7 t ha-1) and the hybrid PM46 (14.0 t ha-1), while Mombaça and Tanzania yielded 12.5 and 11.0 t ha-1, respectively. Leaf organic matter digestibility and leaf DMY for PM40 and PM46 genotypes exceeded the mean (> 656 g kg-1 and > 11.7 t ha-1, respectively). For this reason, PM40 and PM46 can be considered promising P. maximum genotypes for use as forage for grazing systems in the Brazilian savannah.